PELAKSANAAN PEMBINAAN NARAPIDANA WANITA DI LEMBAGA PEMASYARAKATAN KLAS II B KOTA PEKANBARU - Rotua lilis; Emilda Firdaus; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
In order to provide guidance to women inmates, placement of women do classification on the basis of: Age, Gender, length of criminal sentences, type of crime and other Criteria according to the needs or developmental coaching. And coaching female prisoners held in prisons in female prisons, according to article 12 paragraph (1) and (2) of Law No. 12 Year 1995 on Corrections. Similarly, in Government Regulation No. 31 Year 1999 on the Development and Mentoring inmates and correctional further regulated in the Decree of the Minister of Justice of the Republic of Indonesia Number: 02-1990 PK.04.10 regulating Development Patterns Prisoners / Prisoners. However, in practice prisoners are still mixed. This is because the provisions of the law governing the protection aspects of women only in the conceptual level only, not followed by the implementation of such provisions in the field. Action unites women prisoners in Penitentiary II Class B Pekanbaru, not just a State denial of the rights of prisoners, but also a state violation of the provisions of Regulation Legislation.The formulation of the problem in this research is how the Implementation Guidance for Women in Prison Inmates class II B Pekanbaru, what are the obstacles in the process of development of female prisoners in Penitentiary II Class B Pekanbaru and how efforts to overcome obstacles in the process of coaching women. This type of research is research sociological analysis of law enforcement training female prisoners in Penitentiary II Class B Pekanbaru. The nature of the said research Descriptive research into the conduct of an event certain areas at certain times that have a picture of the initial data issues to be investigated, especially with regard to the title.In the implementation guidance to women prisoners are still many obstacles, this is caused by lack of facilities and infrastructure, sertaa nggaran for guidance from the government that can not meet the requirements of Class II B Penitentiary Pekanbaru, so Penitentiary II Class B Pekanbaru, taking policy itself in the Implementation guidance on female inmates, and using the budget of the government as well as possible, in order to achieve optimal development.